Klimaszewskia, a new genus of the tribe Tyrini from the Oriental region (Coleoptera: Staphylinidae: Pselaphinae) - Yin, Zi-Wei; Zhang, Wen-Xuan (Zootaxa, 2021)
A new genus and species of the pselaphine tribe Tyrini, Klimaszewskia punctata gen. et sp. nov., is described and illustrated from Java, Indonesia. Klimaszewskia gen. nov. differs from all other genera of Tyrini primarily by the long, extended maxillary palpus having the fourth palpomere that is mesally expanded near the base, and has an elongate and narrowed apical region, combined with the presence of an antebasal sulcus of the pronotum, and the long first visible tergite. A single female with much larger body size from Nepal, representing a second species of the new genus, is briefly characterized but left unnamed.